Targeting inflammatory pathways in myocardial infarction. (17th June 2013) - Christia, Panagiota; Frangogiannis, Nikolaos G.
Abstract Acute cardiomyocyte necrosis in the infarcted heart generates damage‐associated molecular patterns (DAMPs), activating complement and Toll‐Like Receptor (TLR)/Interleukin (IL)‐1 signalling and triggering an intense inflammatory reaction. Infiltrating leucocytes clear the infarct from dead cells, while activating reparative pathways that lead to formation of a scar. As the infarct heals the ventricle remodels, the geometric, functional and molecular alterations associated with postinfarction remodelling are driven by the inflammatory cascade and are involved in the development of heart failure. Because unrestrained inflammation in the infarcted heart induces matrix degradation and cardiomyocyte apoptosis, timely suppression of the postinfarction inflammatory reaction may be crucial to protect the myocardium from dilative remodelling and progressive dysfunction. Inhibition and resolution of postinfarction inflammation involve mobilization of inhibitory mononuclear cell subsets and require activation of endogenous STOP signals. Our manuscript discusses the basic cellular and molecular events involved in initiation, activation and resolution of the postinfarction inflammatory response, focusing on identification of therapeutic targets. The failure of anti‐integrin approaches in patients with myocardial infarction and a growing body of experimental evidence suggest that inflammation may not increase ischaemic cardiomyocyte death, but accentuates matrix degradation causing dilative remodelling. Given the pathophysiologic complexity of postinfarction remodelling, personalized biomarker‐based approaches are needed to target patient subpopulations with dysregulated inflammatory and reparative responses. Inhibition of pro‐inflammatory signals (such as IL‐1 and monocyte chemoattractant protein‐1) may be effective in patients with defective resolution of postinfarction inflammation who exhibit progressive dilative remodelling. In contrast, patients with predominant hypertrophic/fibrotic responses may benefit from anti‐TGF strategies.